L’établissement du Runde Berg et les sites de hauteur en territoire alaman (ive-ve s. apr. J.-C.) - Dieter Quast (Gallia)
The site of the Runde Berg is settled at the top of a hill of the north slope of the Swabian Jura. This area which is part of the Roman province of Germania Superior in the Early Empire is progressively abandoned by the Roman administration in the second half of the 3rd c. AD, whereas new immigrants belonging to the Elbe Germanic culture settle: the Alamanni. The region takes the name of Alamannia in the 4th c. Situated in the heart of this area the Runde Berg becomes a hill settlement from the second half of the century. During a first phase, wich lasts until the mid-5th c., the occupants seem to have economic and cultural contacts with the middle Danube valley, in the present central part of Germany and the Roman provinces of Eastern Gaul, as shown by elements of material culture found on the site. In the second half of the 5th c., while most of the hilltop settlements in Alamannia are abandoned, the occupation of the Runde Berg expands and reaches its peak. The hilltop is partly delimited by a double palisade, while finds show the high social status of the occupants, and attest that the previous long-range contacts went on. The site is suddenly abandoned around 500 AD, perhaps in connection with the Frankish conquest of Alamannia.